A new genus and species of tachinid flies from Iran (Diptera, Tachinidae, Goniini) - Gilasian, Ebrahim; Ziegler, Joachim; Tóthová, Andrea; Parchami-Araghi, Mehrdad (European Journal of Taxonomy, 2021)
Susamyia Ziegler & Gilasian gen. nov. and its type species Susamyia mira Ziegler & Gilasian gen. et sp. nov. are described from southwestern Karkheh National Park and southeastern Jazmourian Wetland of Iran. Drawings of terminalia and head of the male as well as images of habitus, head and egg are provided. Susamyia gen. nov. is incorporated into the identification key to the Palearctic tachinid genera of Tschorsnig & Richter (1998). The systematic position of Susamyia gen. nov. in the tribe Goniini (Exoristinae) is discussed in light of molecular analyses based on the ribosomal genes 16S, 18S and 28S, and the egg type of females. The morphology of the microtype eggs was studied and compared with that of other Goniini, but proved too unreliable to be included in the phylogenetic analysis. Susamyia gen. nov. is believed to be most closely related to the goniine genera Gymnophryxe Villeneuve, 1922, Palesisa Villeneuve, 1929 and Prosopodopsis Townsend, 1926.